Functional food mixtures: inhibition of lipid peroxidation, HMGCoA reductase, and ACAT2 in hypercholesterolemia‐induced rats - Mohd Rosmi, Noor Syafiqa Aqila; Shafie, Nurul Husna; Azlan, Azrina; Abdullah, Maizaton Atmadini (John Wiley and Sons, 2021)
Mixtures of selected functional foods (MSFF) were composed of nattokinase (fermented soybean), red yeast rice extract, Ginkgo biloba, oat fiber, garlic, bee pollen, and propolis as anti‐hypercholesterolemic were studied. The goal of this study was to determine the bioactive compounds in these mixtures and their cholesterol‐lowering potential effects (biochemical profiles, lipid peroxidation, liver tissue histopathology, and enzymatic activity analysis; HMGCoA reductase and ACAT2. The LC‐MS/MS analysis showed that bioactive compounds such as Monacolin K, naringin, tocopherol, and glutamate, which have potential as anti‐hypercholesterolemic agents, were present in these functional food mixtures. MSFF supplementation at 50 mg/kg 100 mg/kg and 200 mg/kg showed substantial reductions in serum lipid profiles (TC and LDL) (p < .05). The serum liver profiles of AST (115.33 ± 8.69 U/L) and ALT (61.00 ± 1.00 U/L) were significantly reduced (p < .05) with MSFF supplementation at 200 mg/kg. MDA lipid peroxidation has also decreased significantly (p < .05) in serum (3.69 ± 0.42 μmol/L) and liver (15.04 ± 0.97 μmol/mg) tissues and has been shown to protect against hepatic steatosis. The significant (p < .05) inhibition activity of HMGCoA reductase (163.82 ± 3.50 pg/ml) and ACAT2 (348.35 ± 18.85 pg/ml) was also attributed by the supplementation of MSFF at 200 mg/kg.